TEACHING GRAMMAR FOR COMMUNICATIVE COMPETENCE - Qudratova Samira Botir qizi (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
While grammar is crucial for learning languages, conventional approaches often emphasize accuracy at the expense of fluency, which can obstruct learners' ability to communicate effectively. This article examines the significa8nce of incorporating grammar teaching within a communicative language teaching (CLT) framework to enhance grammatical competence in real-life contexts. To foster communicative skills while ensuring grammatical precision, educators can transition from rigid, rule-focused instruction to lessons grounded in context.The text outlines essential techniques, including task-based learning, inductive approaches, and valuable interactions. It also emphasizes the advantages of integrating grammar into problem-solving tasks, role-playing activities, and the use of authentic resources. By transforming grammar instruction into a more engaging and practical experience, teachers can equip learners with the skills necessary for effective communication in everyday scenarios. The article underscores the importance of grammar.